Investigating the functionality of African-specific variants in the TGFB1 regulatory region and their potential role in HIV-associated kidney complications - Buys, Joy-Mari (Department of Human Biology, 2017)
Transforming growth factor beta-1 (TGF-β1) is a cytokine involved in immune modulation and tissue regeneration and has a polymorphic TGFB1 promoter. African-specific single nucleotide polymorphisms (SNPs) have been identified in the TGFB1 promoter and they occur at higher frequencies in South Africans with African-genetic ancestry (≈17%) compared with West and East African genomes (<5%). However, the functional significance of these SNPs has only been partially explored. In this study it was hypothesized that higher frequencies of immunemediated disease complications in South Africans, such as HIV-associated nephropathy (HIVAN), may be influenced by functional genetic variations in TGFB1. To address this, the African-specific TGFB1 haplotypes containing singular, or combinations of, -1287 G>A (rs11466314), -1154 C>T (rs35318502), -387 C>T (rs11466316) and -14 G>A (rs9282871) were investigated for their effect on TGFB1 promoter activity. Briefly, an extended TGFB1 regulatory region driving a luciferase reporter was used as a template to generate six TGFB1 promoter haplotypes (referred to as H-1 through H-6 in this thesis) by site-directed mutagenesis and luciferase activity was used to measure promoter activity. The functional TGFB1 -1347 C>T variant was also investigated (H-5 and H-6 containing -1347 C and T alleles, respectively) because all four of the African variants more frequently co-occurred with the previously reported "lower expressing" TGFB1 -1347 C variant (H-1 through H- 4). Transient transfection of the TGFB1 promoter reporter constructs in two renal cell lines (RCC4+VHL and Caki- 2) showed no difference between -1347 C (H-5) and T (H-6) basal promoter activity. Having at least one African variant resulted in ~5-fold loss of basal TGFB1 promoter activity in renal cells when compared to the most common haplotype (H-5) (p<0.05). The repressive effect is mainly attributed to the -387 T variant (H-1) as the addition of other African variants on this haplotype showed no additional TGFB1 promoter repression. The repressive effect of the TGFB1 -387 T variant was maintained even after in-vitro treatment of transfected renal cells with recombinant human TGF-β1 (rhTGF-β1). To determine whether the African-specific TGFB1 promoter haplotypes (H-AFR), containing TGFB1 -387 T and tested in luciferase assays, also impact on endogenous TGF-β1 protein levels, western blot analysis was performed on human dermal fibroblasts from patients who had been genotyped. Similar to the promoter studies, basal TGF- β1 protein levels in cells with the H-AFR were ~47% lower compared to cells without (p=0.04) and no difference was seen in response to hrTGF-β1. Interestingly, when western blots were screened for phosphorylated Smad3 (pSmad3) protein levels, as an indicator of the activated TGF-β1 canonical pathway, similar pSmad3 levels were observed under basal and hrTGF-β1 stimulated conditions for all haplotypes (p>0.05). The possible interaction of HIV tat on the African TGFB1 promoter variants was also assessed. Luciferase activity was measured after co-transfecting renal RCC4+VHL and HT1080 fibroblast cells with a HIV Tat expression vector and the H-6, H-5 and H-AFR promoter luciferase constructs. Results showed that the promoter activity for all TGFB1 haplotypes was upregulated in the renal cells (≥1.6-fold; p<0.001). The same result was, however, only observed for TGFB1 haplotypes H-5 and H-AFR in the fibroblast cells (≥1.4-fold; p<0.01). This is interesting because no difference was seen between TGFB1 H-5 and H-6 basal promoter activity. To investigate whether histopathological severity of HIVAN correlated with TGF-β1 staining patterns, immunohistochemistry was performed on 20 renal biopsies from patients with HIVAN. A semi-quantitative "histo" score (H-score) was calculated by multiplying the percentage of positive cells with the intensity of the stain before comparing the scores with control biopsies (HIV-negative, n=3 and HIV-positive without HIVAN, n=3). Compared to the HIV-positive controls the kidney tubules of HIVAN biopsies had higher H-scores. Strikingly, the interstitium of HIVAN samples stained much more prominently (17/18) than both control groups suggesting that TGF-β1 staining in the renal interstitium appear to be specific for HIVAN. In conclusion this study shows that the African-specific haplotypes effect basal TGFB1 promoter activity and TGF-β1 protein levels. However, they do not seem to affect the cytoplasmic TGF-β1/pSmad3 protein levels in response to rhTGF-β1 autocrine stimulation. Immunohistochemistry results suggest that TGF-β1 pathway may be prominently dysregulated in the renal interstitium of HIVAN cases.